If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -2(2x + -1) Reorder the terms: 15 = -2(-1 + 2x) 15 = (-1 * -2 + 2x * -2) 15 = (2 + -4x) Solving 15 = 2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 15 + 4x = 2 + -4x + 4x Combine like terms: -4x + 4x = 0 15 + 4x = 2 + 0 15 + 4x = 2 Add '-15' to each side of the equation. 15 + -15 + 4x = 2 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 2 + -15 4x = 2 + -15 Combine like terms: 2 + -15 = -13 4x = -13 Divide each side by '4'. x = -3.25 Simplifying x = -3.25
| 5w+9.9=4.8+4.8 | | 6b+14=51-5d | | 10x^2-5x-63=6+8x | | 4-3x=-4x-2x+16 | | 3-4(x-2)=7x | | 5+2(m+4)=5(m-3)+10 | | 10+4r=2+5r | | 2v-7=24 | | 2(x-10)-3(x+10)=4x | | 10w-40=48+2w | | .66x-6=-12 | | w(3w-2)-3w(w-3)=w-1 | | 6(x-4)-x=-9 | | 2(a+1)-5(a-1)= | | -6x+10=-4x+18 | | (3/4)x-2=(x/3)+3 | | 6(4-n)=18 | | (3/4)x-2=(x/2)+3 | | 12e-20=16e+16 | | 5x^2+40x-525=0 | | c^2-256=0 | | -17-2x=6-1 | | 4m-5m=5-6m | | 6(x+7)=2(4+x)-3(-2x-5) | | 5-(x+7)+4x=7x-1 | | .25x+2=10 | | 5+6-6n+2n=n+1 | | (7/8)(-x-6)+(3/4)(2x+3)=(-3/8) | | 5q-6=54-q | | 13=5m-3 | | 12-(-3)+40= | | 3t^2-4t-12=0 |